UPAYA PENCEGAHAN STUNTING DENGAN EDUKASI PENTINGNYA ASI, MPASI DAN MAKANAN BERGIZI - Asroful Kadafi; Beny Dwi Pratama; Ratih Christiana; Silvia Yula Wardani; Ardin Nurfaizin; Okta Setiawan; Ivan Afria Listiana Putra; Taupik Hidayat (LPPM Universitas Bina Bangsa, 2023)
Stunting is one of the problems currently being the focus of the Indonesian government. The problem of failure to thrive in children caused by chronic malnutrition must receive special attention and intervention so that the number does not increase. Stunting prevention efforts can be started from the surrounding environment through education from related parties. This encourages the service team to help problems that exist in the community. The method of implementing community service begins with obtaining permits and initial identification of stunting problems in Bener Village, Saradan District, Madiun Regency, the second stage together with the village determines the parties involved in the activity, the third stage determines activity targets, the fourth stage conducts outreach about MPASI and nutritious food, and the fifth stage is evaluating activities. The results of the evaluation showed that after being given education, the target community gained knowledge about solids and nutritious food. It is hoped that this new knowledge will be able to be applied by the target community to provide the needs of solids and nutritious food for the baby